Collective Organizational Engagement & Work Engagement as Anchor Strategies to Sustain Green Organizational Performance A Case Study on Indonesian Organizational Services - Thamrin Muhammad Noor (Inovbiz: Jurnal Inovasi Bisnis, 2021)
It is generally believed that by orchestrating a nomological network to leverage COE which strongly supported by transformative leadership style, Practices in HRM, leadership style and working design could lead to condusive organizational performance. This research is to empirically analyze the antecedents of green organizational performance mediated through Collective Organizational Engagement (COE) and work engagement.   Current study deployed Structural Equation Modeling (SEM) with Amos 24 to statistically investigate proposed hypotheses. Survey is also conducted with questionnaires to collect data with non-probability sampling. Upper-Echelon Leaders, Top-Mid Level Managers and long-Level Employees present as sample from 100 organization as population. Statistical outputs demonstrated that Green Working Design, Green Leadership Behavior and Green HRM Practices significantly showed as the antecedent of COE, GWD and Green HRM Practices also proved as the key factors on Work Engagement. Furthermore, COE and WE play crucial moderating variable on Green Organizational Performance. The study also provided theoretical, research limitation and further research..